Clinical Evaluation Of Urinary Catheterization Practices In Emergency Department And Intensive Care Unit Of A Tertiary Care Hospital - Rajavel.C, Rajavel.C; P T, Kumaresh; Lakshmi, Vijaya S.; Babu k, Dhinesh; Sasikumar. V, Sasikumar. V (Journal of Neonatal Surgery, 2025)
Introduction: Urinary catheterization is a crucial medical intervention, particularly in emergency departments (EDs) and intensive care units (ICUs). Despite its benefits, catheter-associated urinary tract infections (CAUTIs) remain a significant complication, increasing morbidity, hospital stays, and healthcare costs [1, 3,] . The implementation of catheter care bundles has been identified as an effective strategy for reducing CAUTI incidence [5, 8,]. This study evaluates the impact of a catheter care bundle on infection rates and adherence to best practices in a tertiary care hospital. Objectives: To assess the effectiveness of a catheter care bundle in reducing CAUTI incidence in Emergency Department and ICU settings by comparing pre- and post-implementation outcomes. Methods: A prospective observational study was conducted over six months in the Emergency Department and ICU. The study included two phases: a pre-implementation phase (baseline data collection) and a post-implementation phase (following catheter care bundle introduction). The study included 200 patients (100 per phase) meeting specific inclusion criteria. Data on demographics, catheterization practices, maintenance, and CAUTI incidence were collected. The care bundle focused on aseptic insertion techniques and proper maintenance protocols. Statistical analysis was conducted using SPSS, with chi-square and t-tests applied to compare categorical and continuous variables. Results: The study revealed significant improvements post-implementation. CAUTI incidence dropped from 12.5 to 4.8 per 1000 catheter days (p=0.001). Aseptic technique adherence improved from 78% to 96% (p=0.002), and average catheter days decreased from 5.6 to 4.3 (p=0.01). The device utilization ratio reduced from 0.32 to 0.28 (p=0.04), while catheter-free days increased from 2.1 to 3.8 (p=0.03). Despite these improvements, nonadherence to hand hygiene (26.3%) and improper documentation (32.8%) remained challenges. Conclusion: The implementation of a catheter care bundle significantly reduced CAUTI incidence and improved adherence to best practices. Training, continuous monitoring, and reinforcing hygiene protocols played crucial roles in these improvements. However, challenges such as hand hygiene compliance and documentation persist and require further attention. Ongoing education, accountability, and targeted interventions are recommended to sustain and enhance patient safety in high-risk clinical settings.